Effect of erector spinae plane block for rib fractures on postoperative analgesia for elbow surgery: A case report - Bhattarai, Prajjwal Raj; Sharma, Achyut; Sharma, Rinku; Sharma, Apurb (Birat Journal of Health Sciences, 2020)
The erector spinae plane block is an emerging technique for analgesia. It has shown to provide reliable analgesia in abdominal and thoracic surgery. Erector spinae plane block may be efficacious for analgesia of pain in the upper limb. The advantage of this modality would be in a patient with polytrauma with rib fractures and upper limb fracture/injury as it assists in the physiotherapy of the chest and upper limb.